Obraz druhého: příklady z francouzských dějin (kontext a proměny) - Pavel Sitek (AntropoWebzin, 2010)
Following text deals with the problems of relationships between the French society and “the other”. The emphasis is put on the context and discourses of political elites during the 19th and 20th century that influenced the creations and the transformations of structured representations not only of “the other” but also of “itself”. “The other” was connected to different menaces and anxiety about “(national) identity”, with a cultural and social thread. In this article we propose three examples to demonstrate that perception of “the other” changes during the time in dependence on the context.